PEMBANGUNAN WEBSITE BERBASIS CRM GUNA PENCAPAIAN TUJUAN PERUSAHAAN STUDI KASUS PT.GLOBAL FORTUNA - Sikumbang, Erma Delima; Mazia, Lia (LPPM Universitas Nusa Mandiri, 2014)
Customer Relationship Management (CRM) is a strategy of acquiring and retaining customers by taking into account the development of technologies relevant to the CRM application. With a CRM strategy, companies can establish a good relationship with customers. Maintaining customer loyalty (customer loyalty) must be carried out by the company in the long term to prevent the occurrence of a condition in which the product is lost in the absence of an